An Injectable Hyaluronic Acid-Based Composite Hydrogel by DA Click Chemistry With pH Sensitive Nanoparticle for Biomedical Application - Hu, Xiaohong; Gao, Ziyu; Tan, Huaping; Wang, Huiming; Mao, Xincheng; Pang, Juan (Frontiers in Chemistry, 2019)
Hydrogels with multifunctional properties attracted intensively attention in the field of tissue engineering because of their excellent performance. While object-oriented design had been supposed to an effective and efficient method for material design as cell scaffold in tissue engineering. Therefore, a scaffold-oriented injectable composite hydrogel was constructed by pH-sensitive bifunctional nanoparticle for growth factor delivery and Diels-alder click crosslinked hyaluronic acid hydrogel as matrix in the work. Firstly, pH-sensitive bifunctional nanoparticle with homogeneous sphere morphology and biphase structure was fabricated by combined W/O/W technique and in situ polymerization. The growth factor could be encapsulated into the nanoparticle by absorbance, and its release behaviors were dependent on pH value of released medium. Bioactivity of the released growth factor was evaluated by in vitro cell culture method. Secondly, in order to synthesize flexible and biocompatible hydrogel, HA-furan, HA-furan-ADH and HA-furan-CHO were with furan substitute degree of 17%, ADH substitute degree of 17%, CHO substitute degree of 21%. Hydrogel was fabricated and enhanced by two kinds of crosslinking points, namely, dynamic covalent and reversible Diels-alder click chemistry. The properties of hydrogel like gelation time and swelling ratio were influence by pH value and polymer concentration. Thirdly, composite hydrogel was formed by in situ polymerization, which exhibited acceptable mechanical property as a scaffold for biomedical field. Lastly, in vitro evaluation from viability, DNA content and cell morphology results confirmed that hydrogels could maintain cell activity and support cell growth, and further composite hydrogel possessed better properties.